Pengaruh Pemberian Morinda Citrifolial. Terhadap Fungsi Ginjal Diabetes Nefropati pada Tikus Sprague Dawley yang Diinduksi Streptozotocin (S T Z) - Fithriana, Dina (STIKES Mataram, 2015)
Background : Morinda citrifolia L (mengkudu) already known scientifically contain antioxidant, poliphenol and flanovoid which reducing oxidative stress and regenerate the kidney junction measured by albumin urin level, Nitrit Oxide level and laminin expression. Purpose: The purpose ofthis experiment was to proving the Morinda citrifolia effect with dose ( I O, 20, 40, 80 mg/dL) to lowering albumin urin level, increasing NO level and reducing laminin expression in messangial in streptozotocin-induced diabetic nephropathy Sprague dawley rats. Design and method: This experiment using the post test only control group design. Sprague-dawley rat was induced streptozotocin in 4 Omg/kg WB doses. A/ter eight weeks, the rats treated with Morinda citri/olia extract in four doses (lO;2(),'40,'80mg/dL). The purpose of this study was to determine albumin urin level, NO level and laminin expression. The data will be analyzed using SPSS.l7 software using oneway-ANO VA test and post hoc LSD test, Kruskal-Wallis test and Mann- Whitney U test and Spearmans Rho test with confidence interval 95% (p,0,05) Result .' The statistic analysis from rats treated with morinda extract and control group resulted a differeiice in albumin urin level, NO level, laminin expression, correlation between albumin urin level with NO level and laminin expression that all variables statistically significant (p